Teacher Questions And Student Responses In The Speaking Class Of Non-Formal Education - Fajar Rahmawati, Safitzal; Fauziati, Endang; Sumardi, Sumardi (CV. Inara, 2024)
Giving questions in a speaking class is necessary to encourage students to speak in the target language. It is challenging for the teacher to carry out suitable questions in the teaching learning process. This study investigates the types of teacher questions, how the students respond to the teacher questions, and which teacher question type encourages and discourages students from speaking along with the reasons. A case study was used as a research method to explore teacher questions' role in creating active learning as seen from student responses in an English course in Indonesia. The data were gathered through observation, documentation (audio-recording and field notes), and interviews. The result shows that display/close-ended question types became the most posed questions by the teachers and were more influential to students’ speaking skills because they were frequently asked questions and responded to by the students excitedly as a group or individually. However, it was also less influential because the students received no responses in several times and the teachers gave excessive responses. Meanwhile, the choral response became the most response that students gave. This study underscores that display/close-ended questions are good enough for beginners to encourage them to speak but should not be excessive.